STUDY OF HIV CONTAMINATION MANNERS IN 22 AIDS PATIENTS IN IRAN AND INFLUENCE OF SEXUAL BEHAVIOR IN THIS CONTAMINATION - A. Kazemy; M. Mohraz (Tehran University of Medical Sciences, 2000)
In a study to determine the influence of sexual behaviour to HIV contamination, in 22 patients infected with AIDS in Iran, this survey was conducted. The subjects were 21 male and one female. One of the male patients was from Uganda, another was an intravenous drug addict, and one patient has been abroad for sometime. One of the patients had been abroad and received blood there, and other patients, had blood disease. This result showed that sexual behaviour was not important as to HIV contamination in this group.